Nutritional Status Positive Deviance Among Toddlers from Economically Disadvantaged Families in Namosain Village, Alak Health Center, Kupang - Luju, Paulus Hangga; Oematan, Grouse T S; Gustam, Tasalina Y P (Timorese Journal of Public Health, 2025)
Stunting is generally experienced by vulnerable or at-risk families, such as in families with low or poor economy. However, toddlers who have good nutritional status can also be foexample of a positive deviation that has been successfully implemented by underprivileged families. This study aims to reveal the factors why poor families can have toddlers with good nutritional status. This type of research is qualitative with a case study design, with samples taken from poor families who have toddlers without stunting in Namosain sub-district. The selection of samples in this study used a purposive sampling technique based on case criteria. The tools used in this study included questionnaires as well as recording and documentation tools. Data analysis was carried out qualitatively based on information obtained from in-depth interviews with informants. The results of the study showed that the pattern of feeding, personal hygiene, and health services among poor families was good. Families were able to provide and regulate a variety of nutritious foods for toddlers by choosing nutritious foods that were easily accessible to mothers of toddlers. Families also always pay attention to personal hygiene and health services for toddlers, thus supporting their nutritional status. Cadres and health workers play a role in monitoring the nutritional status of toddlers, providing counseling on nutrition, and dealing with nutritional problems. Positive deviance behavior needs to be socialized to the community through family empowerment and various experiences between families that show positive deviance, with support from the local health service and community health centers to improve health levels.